Pengaruh Akuntabilitas dan Transparansi Laporan Keuangan terhadap Motivasi Berdonasi Jemaah Masjid di Surabaya - Taufikkurrahman, Diki; Wibowo, Hari Santoso; Diki, Diki Taufikkurrahman (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2023)
Changes The aim of this research is to analyze the influence of accountability and transparency in financial reports on the motivation to donate among mosque congregants in Surabaya. The population in this study consists of mosque congregants in the city of Surabaya, totaling 75 respondents spread across 28 mosques. The type of data used in this study is quantitative data. The data source obtained in this research is primary data obtained from questionnaire responses. The data collection techniques used in this study include an overview of the research object, descriptive analysis, validity testing, reliability testing, and hypothesis testing. The research findings indicate that there is a positive and significant influence of accountability on congregants' donation motivation, with a path coefficient value of 0.650, a t-statistic value of 5.446 (>1.96), and a p-value of 0.000, which is smaller than 0.05. These findings suggest that the higher the level of mosque accountability, the more motivated congregants are to donate. Transparency does not affect congregants' donation motivation, with a path coefficient value of 0.110, a t-statistic value of 0.854 (<1.96), and a p-value of 0.393, which is greater than 0.05. The findings indicate that there are other factors influencing congregants' donations